Ttermination of contract and destination of data and content generated by users of digital services - Cámara Lapuente, Sergio (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
During the use of digital content and services made available to the consumer by different traders and platforms, users provide and create large amounts of data. The legal treatment of control over the destination of these data currently splits into two pieces of legislation: on the one hand, in the case of personal data, the 2016 (EU) General Data Protection Regulation (GDPR) will apply; on the other hand, in the case of user-generated content other than personal data, the rules of the recent Directive (EU) 2019/770 of 20 May 2019 on contracts for the supply of digital content and services (DCSD) will apply after transposition in Member States.This paper analyses the intersection of the rules on personal data protection with the rules on the contractual protection of the consumer at the time of the extinction of this type of contract by means of termination. To this end, it compares the features of the rights to erasure, to be forgotten and to portability of the Regulation with the new rights to prevent further use of data and to retrieve them established in the Directive, and critically concludes that the latter may have little impact due to their reduced scope of application, the limited powers and the excessive exceptions finally incorporated in one of the central articles of Directive 2019/770.
Keywords: digital contents; digital services; termination; contract of supply; personal data; portability; right to erasure; right to be forgotten; Directive (EU) 2019/770; General Data Protection Regulation; conformity; user generated contents; consumer